SOME PROBLEMS OF OIL AND GAS ACCUMULATION AS RELATED TO THE EVOLUTION OF CARBONATE SEDIMENTATION - Kuznetsov V.G. (My University, 1990)
The distribution of hydrocarbon reserves in carbonate strata in the geologic section is analogous in principle to that of the total hydrocarbon reserves, although there also are important differences. First, the fraction of hydrocarbon reserves in the Paleozoic is three to five times smaller, so the Mesozoic peak becomes still sharper. Nor are the hydrocarbon reserves directly or inversely related to the volume of carbonate deposits of the corresponding erathems, which clearly decreases with time. The second difference is that the hydrocarbon reserves in carbonate deposits are more clearly concentrated within narrower stratigraphic intervals. The third feature is that the epochs of maximum hydrocarbon accumulation do not coincide in time. The next feature is that the peaks of hydrocarbon accumulation in carbonate strata are closer in time to the corresponding peaks for organic carbon and bitumenoids. Thus, as stratified hydrocarbon reservoirs developed through time, the massive and, apparently, the lithologically confined varieties have become more important.
Keywords: Paleozoic; Mesozoic; Палеозой; Mesozoic; Paleozoic; Мезозой